2016
DOI: 10.1039/c6cc01299j
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical rationalisation for the mechanism of N-heterocyclic carbene-halide reductive elimination at CuIII, AgIII and AuIII

Abstract: A dichotomy in carbon versus bromide reductive elimination in CuIII–NHC complexes is rationalized by computational methods (DFT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…It follows that Pd­(P t Bu 3 ) 2 is a stronger Lewis base than other substrates, as is evident from the fact that Pd­(P t Bu 3 ) 2 possesses a higher-lying HOMO with an energy level of −4.00 eV; the HOMO energy levels for the vinylstannane and the alkyne are calculated to be lower in energy (−6.92 and −7.85 eV, respectively). The antibonding character of the HOMO of the linear transition-metal complexes with d 10 configuration causes these complexes to be basic (Figure b) . However, this basicity is affected by the nature of the L ligands.…”
Section: Resultssupporting
confidence: 86%
“…It follows that Pd­(P t Bu 3 ) 2 is a stronger Lewis base than other substrates, as is evident from the fact that Pd­(P t Bu 3 ) 2 possesses a higher-lying HOMO with an energy level of −4.00 eV; the HOMO energy levels for the vinylstannane and the alkyne are calculated to be lower in energy (−6.92 and −7.85 eV, respectively). The antibonding character of the HOMO of the linear transition-metal complexes with d 10 configuration causes these complexes to be basic (Figure b) . However, this basicity is affected by the nature of the L ligands.…”
Section: Resultssupporting
confidence: 86%
“… It is interesting to note that the reverse reaction occasionally afforded 2-halogenoimidazolium salts by reductive elimination for NHC metal complexes, and for instance [(IMes)­I]­I 3 was isolated by thermal decomposition of [(η 5 -C 5 H 5 )­Co­(IMes)­I]­I 3 , whereas [(IDipp)­I]­I 3 , [(IDipp)­Br]­OTf, and [(IDipp)­Cl]­SbF 6 were isolated from the copper­(I) complex [(IDipp)­CuX] (X = I, Br, Cl) in the presence of Selectfluor (1-chloromethyl-4-fluoro-1,4-diazoniabicyclo[2.2.2]­octane bis­(tetrafluoroborate)) as an oxidant . It was suggested that these reactions proceed through oxidation of Cu­(I) to Cu­(II) species followed by C carbene –halogen reductive elimination. , …”
Section: N-heterocyclic Carbene Adducts Of Group 17 Elementsmentioning
confidence: 99%
“…905 It was suggested that these reactions proceed through oxidation of Cu(I) to Cu(II) species followed by C carbene −halogen reductive elimination. 905,906…”
Section: Telluriummentioning
confidence: 99%
“…This difference could be due to the different electronic nature of the ancillary ligand, as a study by Willans, Ariafard, and Fairlamb on the C(carbene)−Br reductive elimination from the copper(III) species [trans-(IMe 2 H 2 )CuBr 2 X] + (210, X = benzyl, Me, vinyl, Ph, CF 3 , CN, I, F, Br, and Cl) indicated that the stronger σdonating nature of the X ligands results in higher activation energies of the reductive elimination step. 373 In addition to the aforementioned studies, copper(III) species were also implicated as intermediates in the formation of bis(imidazolium) salts in the reactions of (1-pyridinylimidazol-2-ylidene)silver(I) bromide with copper(II) dibromide (Scheme 81). 374 Willans et al found that the equimolar reaction of (1-pyridinyl-3-allylimidazol-2-ylidene)silver(I) bromide with copper(II) dibromide produced the copper(II)− NHC complex 176 in good yield, whereas changing the molar ratio into 1:2 suppressed the isolation of 176 and resulted in the formation of the 2-bromo-1-pyridinyl-3-allylimidazolium salt (Scheme 81).…”
Section: Complexes Of Coppermentioning
confidence: 99%
“…The reluctance of the (NHC)­copper­(III) species 209 to undergo C–X reductive elimination forms a stark contrast to the facile reductive elimination from 207 . This difference could be due to the different electronic nature of the ancillary ligand, as a study by Willans, Ariafard, and Fairlamb on the C­(carbene)–Br reductive elimination from the copper­(III) species [ trans -(IMe 2 H 2 )­CuBr 2 X] + ( 210 , X = benzyl, Me, vinyl, Ph, CF 3 , CN, I, F, Br, and Cl) indicated that the stronger σ-donating nature of the X ligands results in higher activation energies of the reductive elimination step …”
Section: High-oxidation-state 3d Metal Complexes With Nhc Ligationmentioning
confidence: 99%